The sea, the woman and the fear: the punishment of the feminine transgressor in Mi vida con la ola by Octavio Paz - Gimenes Romero, Joyce Conceicao; Aybar Ramirez, Maria Dolores [UNESP] (Univ Estadual Paulista-unesp, 2019)
The present work proposes a brief reflection on the configuration of the fantastic female character in the tale Mi vida con la ola (1949-50) by Octavio Paz. In view of the mythcritical studies prospect that comtemplates the malefic female ancestral aspect, observe the way that they produce the manifestations of the femme fatale, linked to the waters in the narrative. In this way, we will consider the aesthetic composition of the tale focusing on the contribution of the myth as an important reference for the construction of the feminine archetype of the Terrible Mother in the tale.
Keywords: Fantastic literature; Literary archetypes; Mermaid-woman; Octavio Paz